Overcoming the Problem of Antimicrobial Resistance and Improving Global Health through Telemedicine and Innovations (KIUT Publication, 2025)
According to the World Health Organization (WHO), more than 700,000 people die each year due to infections caused by antibiotic-resistant bacteria. By 2050, this number is projected to reach 10 million. This poses a major threat to the global community, not only from a medical perspective but also from a socio-economic standpoint. Antibiotic resistance negatively affects the reliability of healthcare systems, the duration of disease treatment, and healthcare-related costs.